Planning, Implementation and Problems of Breast Feeding and Infant Nutrition In North Sulawesi - Inda D. Arif; A. S. Ongkie (Paediatrica Indonesiana, 1984)
The effects of nutrition on infant growth and development are put forward. In Indonesia, there are variations in infant feeding practices. Government's nutn'tion promotional efforts are set forth. In North Sulawesi, there is no shortage of food. However, ignorance is prevailing. Shortage of Puskesmas program executors is another handicap. Lack of breast feeding and infant nutrition knowledge among mothers attending Manado's general hospital was ascertained. A better health and nutrition education program inherent to a particular community is deemed necessary. To gain success, the doctor must have sufficient background in public health and methods of organizing a primary care program. A devoted personnel is a must. The Village Community Health Development Program and Village Nutrition Program must grow from the community. Material assistance is equally important.